You are on page 1of 5

Quadratic Formula

Given: ax 2 + bx + c = 0
− b ± b 2 − 4ac
Solve for x: x =
2a

Square of a Sum
(a + b) 2 = a 2 + 2ab + b 2 and
( a + b + c) 2 = a + b + c + 2ab + 2bc + 2ac

Series Formulas

Geometric Series: a, ar, ar2, ar3, … ⇒ a + ar + ar2+ ar3 + …

Sum of first n terms (note: First n terms starts at r0 and goes to rn-1)
1−rn
a + ar + ar2+ ar3 + … + arn-1= a(1 + r + r2+ r3 + … + rn-1)= a ⋅
1−r
Infinite Convergent Series (-1 < r < 1)
1
a + ar + ar2+ ar3 + … = a(1 + r + r2+ r3 + …)= a ⋅
1−r
Arithmetic Series: a, a+d, a+2d, a+3d3, … ⇒ a + (a+d) + (a+2d) + (a+3d) + …

Sum of first n terms (note: First n terms starts at 0d and goes to (n-1)d)
n(n −1)
a + (a+d) + (a+2d) + (a+3d) + … + (a+(n-1)d) = na + d ⋅
2
Special Case for first n integers
n(n −1)
1+2+3+…+n=
2
Definition of ea

an

n =0 n!
= ea

Also – dividing both sides by ea gives



an

n =0
e −a
n!
= 1 (This is the pdf for the Poisson distribution)
Limit Theorems: Let n be a positive integer, k be a constant, and f and g be functions
which have limits at c then:
lim k = k
x →c

lim x = c
x →c

lim kf ( x) = k lim f ( x)
x →c x →c

lim[ f ( x) + g ( x)] = lim f ( x) + lim g ( x)


x →c x →c x →c

lim[ f ( x) − g ( x)] = lim f ( x) − lim g ( x)


x →c x →c x →c

lim[ f ( x) × g ( x)] = lim f ( x) × lim g ( x)


x →c x →c x →c

lim[ f ( x) ÷ g ( x)] = lim f ( x) ÷ lim g ( x) Provided lim g ( x) ≠ 0

[ ]
x →c x →c x →c x →c

lim[ f ( x)] = lim f ( x)


n n
x →c x →c

lim n f ( x) = n lim f ( x) Provided lim f ( x) > 0 when n is even


x →c x →c x →c

Substitution Theorem: if f is a polynomial or rational function, and if rational


denominator at c ≠ 0
lim f ( x) = f (c)
x →c
Derivative
 f (c + h ) − f (c ) 
f ' (c) = lim   Provided this limit exists
h →0
 h 
Alternate Form
 f ( x ) − f (c ) 
f ' (c) = lim  
x →c
 x −c 

Rules of Differentiation
f ( x) f ' ( x)
c (a constant) 0
Power Rule cx n ( n ∈ℜ) cnx n −1

g ( x ) + h( x ) g ' ( x ) + h' ( x )

Product Rule g ( x) ×h( x) g ' ( x ) ×h( x ) + g ( x ) ×h' ( x )


u ( x )v ( x ) w( x ) u ' vw + uv ' w + uvw '

g ( x) h( x ) g ' ( x ) − g ( x ) h' ( x )
Quotient Rule
h( x ) [ h( x ) ] 2
Chain Rule g ( h( x )) g ' ( h( x )) ×h' ( x )

e g ( x) g ' ( x ) ×e g ( x )
g ' ( x)
ln( g ( x ))
g ( x)
a x ( a > 0) a x ln( a )

ex ex
1
ln x
x
1
log b x
x ⋅ ln( b)
sin x cos x
cos x − sin x
′ cf ′(x )
(cf (x ) )

BPP Power Rule (( f ( x)) )′ p


p( f ( x) )
p −1
× f ′( x)

L’Hopital’s Rule
If lim f ( x) = 0 & lim g ( x) = 0 or lim f ( x) = ∞ & lim g ( x) = ∞
x →c x →c x →c x →c
Then
 f ( x)   f ′( x)  g ' ( x) ≠ 0
lim 
x →c g ( x ) 
= lim 
x →c g ′( x ) 
Provided lim
x →c
   
Note: Can be applied multiple times.

Antiderivatives (Integrals) of Some Frequently Used Functions


f ( x) ∫ f ( x )dx
g ( x ) + h( x ) ∫ g ( x)dx +∫h( x ) dx +c

x n +1
x n ( n ≠ 1) +c
n +1
1
ln( x ) +c
x
ex ex +c
ax
a x ( a > 0) +c
ln a
xe ax e ax
xe ax − 2 +c
a a
1 1 −ax 1
e −ax or e or
e ax a ae ax
sin x − cos x + c
cos x sin x + c
Additional integration rules:
∞ n!
For integer n ≥ 0 and real number c > 0 ∫ 0
x n e −cx dx =
c n +1
Integration by Substitution
To find ∫f(x)dx substitute u=g(x), g being differentiable then du =g′(x)dx then we
can rewrite ∫f(x)dx as an integral with respect to the variable u. So if this changes
f(x)dx to h(u)du and H is the antiderivative of h, then
∫ f ( x)dx = ∫ h(u )du = H (u ) + c = H ( g ( x )) + c

Example: Find ∫(x3-1)4/3x2dx – Substitue u= x3-1, so that du=3x2dx or ⅓du= x2dx


7 7
1 u 3 1 3
now the integral can be written as ∫u ∙⅓du = ⅓∫u du = ⋅
4/3
= u (+c) now
4/3

3 73 7
substitute back the u= x3-1 gives the final result ∫(x3-1)4/3x2dx = 1/7(x3-1)7/3(+c)

Integration by Parts
If you have an integral of the form ∫ f ( x) ⋅ g ′( x)dx then do integration by parts
∫ f ( x) ⋅ g ′( x)dx = f ( x ) g ( x ) − ∫ f ′( x ) ⋅ g ( x ) dx

Use when ∫ f ′( x) ⋅ g ( x)dx is easier than ∫ f ( x) ⋅ g ′( x)dx


For a definite integral
f ( x ) ⋅ g ′( x ) dx = [ f ( x ) g ( x )] a − ∫ f ′( x ) ⋅ g ( x) dx
b b

b
a a